Les intellectuels pacifistes allemands et la « suggestion de la guerre » - Philippe Alexandre (Recherches Germaniques)
Analyzing the roots of war and identifying ways to overcome it are two key dimensions of both the ethical thinking and action of pacifists. This paper will therefore examine the situation prevailing in Germany prior to the First World War. Among the intellectuals who at that time supported the pacifist movement, publicists and jurists played a leading role alongside pastors and pedagogues. Using contemporary sociological concepts, they sought to demonstrate that the “suggestion” of war through printed media posed a danger. In order to establish their own audience, they founded associations and published journals and pamphlets. However, in the end, the diverse shapes in which suggestion came and the complexity in decision-making prevailing at the outbreak of war made it impossible to determine the exact influence of the press on the public opinion and decision-makers.